Economic Monitoring Report to the Ad Hoc Liaison Committee - World Bank (Washington, DC, 2015)
This report covers two distinct subjects. Chapter I of the report, as has been the norm with the World Bank Ad Hoc Liaison Committee report, focuses on the assessment of recent macroeconomic and fiscal developments and government policies in West Bank and Gaza. Chapter II presents an analysis of Gazas stark economic decline over the past 20 years and its human impact. It also presents a mix of policies that should ensure sustainable development of the Gaza strip and put an end to human suffering therein. The report also contains an annex which provides an overview of progress in meeting the pledges made for Gazas reconstruction at the October 2014 Cairo Conference. Although the connection between the chapters of this report may not be obvious as they treat a diverse set of issues facing the Palestinian economy and public finances, together they provide insights into key policy and institutional development actions and reforms, which need to be taken by the Palestinian Authority, the Government of Israel, and the donor community to reverse the recent and worrisome slowdown in economic growth, to enable effective and efficient management of public finances in order to avoid a dangerous fiscal crisis and to support inclusive economic growth and poverty reduction.